The loyal lieutenant : leading out Lance and pushing through the pain on the rocky road to Paris - Hincapie, George, 1973- (William Morrow, an imprint of HarperCollins Publishers, 2014)
American cyclist "Big George" Hincapie-- a record seventeen-time Tour de France participant, Olympian, and key witness in the Lance Armstrong doping case-- offers an insightful account of his esteemed career and a sports era defined by performance-enhancing drug use. Hincapie speaks openly about his relationship with Armstrong, how he himself began doping, and why he quit long before the headline-making revelations. His personal evolution is the journey of a man dedicated to coming clean about his past and to restore honor to the sport he loves.